HR-GO: I. comprehensive NLTE abundance analysis of the Cetus stream - Sitnova, T. M.; Yuan, Z.; Matsuno, Tadafumi; Mashonkina, L. I.; Alexeeva, S. A.; Holmbeck, E.; Sestito, F.; Lombardo, L.; Banerjee, P.; Martin, N. F.; Jiang, F. (Astronomy and astrophysics, 2024)
Context. Dwarf galaxy streams encode vast amounts of information essential to understanding early galaxy formation and nucleosynthesis channels. Due to the variation in the timescales of star formation history in their progenitors, stellar streams serve as ‘snapshots’ that record different stages of galactic chemical evolution. Aims. This study focusses on the Cetus stream, stripped from a low-mass dwarf galaxy. We aim to uncover its chemical evolution history as well as the different channels of its element production from detailed elemental abundances. Methods. We carried out a comprehensive analysis of the chemical composition of 22 member stars based on their high-resolution spectra. We derived abundances for up to 28 chemical species from C to Dy and, for 20 of them, we account for the departures from local thermodynamic equilibrium (NLTE effects). Results. We confirm that the Cetus stream has a mean metallicity of [Fe/H] = −2.11 ± 0.21. All observed Cetus stars are α enhanced with [a/Fe] ≃ 0.3. The absence of the α-‘knee’ implies that star formation stopped before iron production in type Ia supernovae (SNe Ia) became substantial. Neutron capture element abundances suggest that both the rapid (r-) and the main slow (s-) processes contributed to their origin. The decrease in [Eu/Ba] from a typical r-process value of [Eu/Ba] = 0.7-0.3 with increasing [Ba/H] indicates a distinct contribution of the r- and s-processes to the chemical composition of different Cetus stars. For barium, the r-process contribution varies from 100 to 20% in different sample stars, with an average value of 50%. Conclusions. Our abundance analysis indicates that the star formation in the Cetus progenitor ceased after the onset of the main s-process in low- to intermediate-mass asymptotic giant branch stars but before SNe Ia played an important role. A distinct evolution scenario is revealed by comparing the abundances in the Ursa Minor dwarf spheroidal galaxy, showing the diversity in - and uniqueness of - the chemical evolution of low-mass dwarf galaxies.
Online verfügbar: 18. Oktober 2024
Gesehen am 28.05.2025